Pengembangan Teknologi Tepat Guna: Pembuatan Sensor Pendeteksi Api Sederhana sebagai Bentuk Pengabdian Masyarakat - Collins, Valentina; Imelia Puspitasari, Fransiska; Miranda, Miranda; Febriyanti, Dini; Nurjanah, Isnawi; Angel Sulistyo, Helen; Dias Firmansyah, Oktavian; Mahmud, Mahmud; Mustapha Salisu, Ibrahim; Yudhistira, Bara (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Fire is a common disaster that can cause significant material and human losses. To improve community preparedness in Dukuh Sosogan, Rejosari Village, Gondangrejo District, Karanganyar Regency, a community service activity was conducted involving training on making a simple fire detection sensor. The sensor was assembled using basic electronic components such as photodiode, transistor, resistor, LED, buzzer, and a 9-Volt battery. Through socialization and training with the local youth organization (Karang Taruna) and village officials, the community was taught how to assemble, test, and use the sensor for early fire detection. The sensor demonstrated quick response and effective alarm signaling. This activity not only raised awareness and preparedness against fire hazards but also empowered local youth to independently develop appropriate technology. This program is expected to help prevent fires earlier and minimize their negative impacts.